Resiliência na adolescência : género e a idade fazem a diferença? - Simões, Celeste (2019)
The goal of this study was to analyze the relationship between a group resilience associated resources in a group of Portuguese adolescents as well as with gender and age. A total of 5695 adolescents attending the 8th, 10th and 12th grades enrolled in the HBSC 2018 study, with a mean age of 15,46 years old (SD = 1,80), 53,9% female, who responded to a resilience scale of internal resources. The various features associated with resilience have moderate to strong correlations with each other. For all resources, the values obtained are at medium-high levels. Girls have significantly higher values in empathy, problem solving, and goals and aspirations, while boys have higher self-efficacy values. Older adolescents, compared to younger ones, have higher values of empathy and goals and aspirations. The results obtained highlight the cumulative effect of protection and the importance of factors such as gender and age in understanding adolescence resilience. Portuguese adolescents have, in general, good levels of internal resources associated with resilience. It is, however, important to develop resilience-promoting programs, bearing in mind that resources associated with resilience are acquired and aggregated over a lifetime, and that more vulnerable groups exposed to more adversity will find it more difficult to trigger this process.